1997
DOI: 10.1021/jf970231y
|View full text |Cite
|
Sign up to set email alerts
|

Erythroagglutinin fromPhaseolus coccineusVar. Alubia:  Chemical Characterization, Sugar Specificity, and Effect on Blood Coagulation Factors

Abstract: Purification of the erythroagglutinin from Phaseolus coccineus var. Alubia was achieved by affinity chromatography on human α1-acid glycoprotein and by ion exchange chromatography. The lectin is a tetrameric glycoprotein of 31 kDa/subunit with 8% sugar by weight, which agglutinates erythrocytes without serological specificity and is devoid of mitogenic activity toward human peripheral lymphocytes. The specificity of the erythroagglutinin is directed toward the Gal (β1−4) or (β1−3) GlcNAc (β1−2) Man (α1-) sacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…These results agree with those reported by Rutella et al, who identified that CD8+ cells exhibited a greater activation response to PHA (33). The P. Vulgaris and P. coccineus lectins recognize Nglycosidically linked oligosaccharides with a minimal octasaccharide structure with the sequence Gal(β1-4)GlcNAc(β1-2) Man(R1-6)[GlcNAc(R 1-2)Man(R1-3)]Man(R1-4) (34)(35)(36)(37)(38). Lectins of 21 and 30 kDa have been described in P. acutifolius var.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results agree with those reported by Rutella et al, who identified that CD8+ cells exhibited a greater activation response to PHA (33). The P. Vulgaris and P. coccineus lectins recognize Nglycosidically linked oligosaccharides with a minimal octasaccharide structure with the sequence Gal(β1-4)GlcNAc(β1-2) Man(R1-6)[GlcNAc(R 1-2)Man(R1-3)]Man(R1-4) (34)(35)(36)(37)(38). Lectins of 21 and 30 kDa have been described in P. acutifolius var.…”
Section: Discussionsupporting
confidence: 92%
“…The P. vulgaris and P. coccineus lectins recognize N-glycosidically linked oligosaccharides with a minimal octasaccharide structure with the sequence Gal(β1−4)GlcNAc(β1−2) Man(α1−6)[GlcNAc(α 1−2)Man(α1−3)]Man(α1−4) ( ). Lectins of 21 and 30 kDa have been described in P. acutifolius var.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of the functional role of carbohydrate residues in coagulation factors has been demonstrated using lectins from Galanthus nivalis agglutinin (Manspecific) (Koyama et al 1991), Sambucus nigra (NeuAc-α -2,6) (Sinha and Wolf 1993), Maackia amurensis (NeuAc-α -2,3) (Sinha and Wolf 1993), peanut (galactose), Datura stramonium (GlcNAc) (Koyama et al 1991), Phaseolus coccineus Var. Alubia erythroagglutinin (Pérez-Campos et al 1997), as well as through glycosydase treatment activating either the extrinsic or intrinsic pathways (Sinha and Wolf 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The hemagglutinating titer is reported as the inverse of the last dilution with agglutinating activity. The sugar specificity of the PNA and each purified isoform was determined by comparing the effect of lactose, at different concentrations, on the hemagglutination induced by each lectin against sialidase-treated human O erythrocytes (Perez-Campos et al, 1997).…”
Section: Methodsmentioning
confidence: 99%